Internet of vehicles : technologies and services towards smart city : 5th International Conference, IOV 2018, Paris, France, November 20-22, 2018, Proceedings /: technologies and services towards smart city : 5th International Conference, IOV 2018, Paris, France, November 20-22, 2018, Proceedings. (2018) - Unknown
No abstract available